Evaluation of Nature-Inspired Algorithms for Battery Parame-ter Estimation in Renewable Energy Generation Systems - Shareef, Hussain; Mainul Islam, Md; Sasi Stephen, Samantha (International Journal of Engineering and Technology, 2018)
Batteries in renewable energy systems suffer problems that affect their service life and quality of performance. Therefore, battery management systems (BMS) are employed in battery-integrated systems to maintain optimal operating conditions by various dynamic impedance based battery models. These models require an accurate model parameter for BMS to work effectively.Â In this paper, two recently developed metaheuristic optimization, namely bird mating optimizer (BMO) and lightning search algorithm (LSA) is used effectively to determine the required parameters of well-known Randleâ€™s battery model.Â Initially, electrochemical impedance spectroscopy (EIS) test for an EnerSys Cyclon lead-acid cell with a rated capacity of 2.5Ah is conducted using EZSTAT-pro Galvanostat/Potentiostat device from Nuvant systems Inc. Next, the Randleâ€™s battery model parameters are obtained by BMO and LSA and its performances are evaluated. The results show that BMO and LSA can accurately find the model parameters. LSA obtains slightly more accurate results than BMO and converges much faster. However, for the same number of iterations, BMO takes less computation time than LSA. The optimized model can be used in BMS for fault finding and condition monitoring.Â Â